The effect of vertical displacements on the runaway electron avalanche in ITER mitigated disruptions - C. Wang; E. Nardon; F.J. Artola; V. Bandaru; M. Hoelzl; the JOREK team (Nuclear Fusion)
In order to prepare the operation of ITER, it is important to estimate the amplitude of the runaway electron (RE) current that could appear following disruptions at large plasma currents. Theoretically, the avalanche gain of RE population on a toroidal flux surface (TFS) is an exponential function of the change in the poloidal magnetic flux Δ ψ on that TFS. However, once a TFS is open, REs on it escape rapidly and can no longer proliferate. It is expected that the vertical motion of the plasma during a disruption could lead to the opening of TFSs as the plasma cross-section is pushed into the wall. The influence of this vertical motion on the RE avalanche gain was rarely considered in previous studies. This study investigates the RE generation in ITER major disruptions and hot vertical displacement events mitigated by the injection of neon and hydrogen, using an axisymmetric 2D model on the JOREK code. Compared to those with a stationary plasma, our simulations show a smaller Δ ψ on a given TFS by the time it becomes open as a result of the vertical motion. The maximum potential avalanche gain is thus reduced from $10^{16}-10^{20}$ without considering the vertical motion to $10^{9}-10^{12}$ , depending on the plasma dynamics during the disruption. In addition, the RE current produced by a typical nuclear seed (∼ 10 mA) at ITER is investigated.